Oral uricase eliminates blood uric acid in the hyperuricemic pig model. - Paulina Szczurek; Nadia Mosiichuk; Jarosław Woliński; Tetiana Yatsenko; Danica Grujic; Liudmyla Lozinska; Marek Pieszka; Ewa Święch; Stefan Grzegorz Pierzynowski; Kateryna Goncharova (PLoS ONE, 2017)
An elevated level of serum uric acid-hyperuricemia, is strongly associated with the development of gout and chronic kidney disease (CKD) which is often accompanied by a significantly reduced glomerular filtration rate (GFR). In the present study, we investigated the extra-renal elimination of uric acid via the intestine in a healthy pig model and the effect of oral uricase therapy on plasma uric acid concentrations in pigs with induced hyperuricemia and CKD. The experiment was conducted on eleven, ten-week-old pigs (n = 11). The porcine model of CKD was developed by performing 9/10 nephrectomy surgery on eight pigs. A stable model of hyperuricemia was established in only five of the eight nephrectomized pigs by frequent injections of uric acid (UA) into the jugular vein. All pigs (three healthy pigs and five CKD pigs) were operated for implantation of jugular vein catheters and the three healthy pigs also had portal vein catheters inserted. Blood uric acid concentrations were measured spectrophotometrically, using the Uric Acid Assay Kit (BioAssay Systems, Hayward, USA). The piglets with CKD received orally administered uricase (treatment) and served as their own controls (without uricase supplementation). Oral uricase therapy significantly decreased plasma uric acid concentrations in pigs with CKD, whereas hyperuricemia was observed in the pigs whilst not being treated with uricase. Urinary uric acid excretion was similar during both the treatment and control periods during the first 8 h and 24 h after UA infusions in the CKD pigs. To demonstrate the elimination of UA via the intestine, the healthy pigs were infused with UA into the jugular vein. The blood collected from the jugular vein represents circulating UA concentrations and the blood collected from the portal vein represents the concentration of UA leaving the intestine. The final (after 2 h) concentration of UA was significantly lower in blood collected from the portal vein compared to that collected from the jugular vein (3.34 vs. 2.43 mg/dL, respectively, p = 0.024). The latter allows us to suggest that UA is eliminated from the blood via the gut tissue.